The Competence of The Eleventh Grade Students at SMA Negeri 5 Tana Toraja in Using Simple Past Tense - Shilfani Shilfani; Hensa Gaber (LPPM UKI Toraja, 2021)
The Competence of The Eleventh Grade Students at SMA Negeri 5 Tana Toraja in Using Simple Past Tense. Thesis English Department Teacher Training and Education Faculty Christian University of Indonesia Toraja. The objective of this research is to find out the competence of the eleventh grade students at SMA Negeri 5 Tana Toraja in using simple past tense. The writer used written test. In order to achieve the objective of this study, The writer used quantitative method. Population from this research is all of the eleventh grade students at SMA Negeri 5 Tana Toraja with the total of students is 264 and divided eight classes. The writer used random sampling. The object of this research was 40 students of the eleventh grade students of SMA Negeri 5 Tana Toraja academic year 2017/2018. The result of the data analysis shows that the competence of the eleventh grade students of SMA Negeri 5 Tana Toraja in using simple past tense got mean score of 47,75. It means that the competence of the students is very bad category.